Bitrophic toxicity of Cry1Ac to Cycloneda sanguinea, a predator in Brazilian cotton. Issue 2 (28th June 2013) - Nakasu, Erich Y.T.; Dias, Simoni C.; Pires, Carmen S.S.; Andow, David A.; Paula, Debora Pires; Togni, Pedro Henrique B.; Macedo, Tainã R.; Sujii, Edison R.; de, Maria F.G.; Fontes, Eliana M.G.
Abstract Insect predators are exposed to the Cry1Ac toxin in Bt cotton fields through several pathways. In this study, we investigated the effects of activated Cry1Ac added to a diet on Cycloneda sanguinea (L.) (Coleoptera: Coccinellidae), which is one of the main predators of non‐target pests in Brazilian cotton. Direct bitrophic exposure of C. sanguinea to Cry1Ac was done by feeding beetles with Aphis gossypii (Glover) (Hemiptera: Aphidae) sprayed with 500 μg per ml Cry1Ac solution. Larval and pupal survival, development time, aphid consumption, and adult longevity were recorded daily. Couples within the same experimental treatment were paired and numbers of eggs laid and hatched per female were recorded daily. Net replacement rate was calculated for each female. During development, a C. sanguinea larva consumed on average 1.8 μg of activated Cry1Ac. No significant differences due to Cry1Ac were observed for any of the response variables, except aphid consumption. Larvae receiving Cry1Ac consumed more aphids than larvae receiving distilled water alone. Additional statistical analyses were conducted to evaluate independence of responses, and for the independent responses, a simple meta‐analysis was conducted to test the null hypothesis that all responses were zero. Nearly all of the response variables were statistically independent. Two pairs of responses were not independent, but the associated multivariate tests were not significant. The meta‐analysis suggested that all effects were not different from random variation around zero and no cumulative effects could be detected. Our results indicated that bitrophic exposure to activated Cry1Ac is likely to have little or no adverse ecological effect on C. sanguinea.